Police Brutality and Custodial Torture in Technological Era: Need for Anti-Torture Law in India - A Critical Analysis - A. Nirmal Singh Heera; Rajasathya K.R; N. Prabhavathi (Indian Journal of Forensic Medicine & Toxicology, 2021)
Police audacity and brutality is not an uncommon phenomenon. It has caught the attention of the publicand the judiciary and eventually a catena of directions was promulgated by the National Human RightsCommissions (NHRC), High Courts as well as the Supreme Court of India right from the ancient era totechnological era. Yet, the menace and inhumane attitude of the police officials have not declined; instead, itis increasing day by day and one step ahead, Tamil Nadu has seen the worst of its effect that has resulted inthe death of an innocent father and his son. This incident has grabbed the attention of not only the State ofTamil Nadu but also the entire Nation. In this situation, the authors intend to analyse the power of the policeto manhandle the public, the liabilities and responsibilities of the police in case of death caused by suchbrutality, and third-degree methods used by the police. This article ponders on the question Does the policehave the power to torture the public for any reasons whatsoever? If so, what are the limitations placed onthe powers of the police while harassing the public? and so on… the authors aspire to analyse the duties ofthe police while making the arrest, the duties of the magistrates while ordering for judicial custody, and theauthors also intend to suggest the remedial measures to curb the menace of lockup deaths.Aim and Scope: To know the powers of the police to torture the public under the guise of investigation, toknow the judicial approach to curtail the menace of torture by the police, and its implications and to knowthe feasibilities of technologies to be implemented during the investigating process.Method: For the purpose of the research, secondary data such as books, articles, news papers, case laws, andlegal provisions of Indian Laws are collected and analysed.Conclusion: In spite of the Constitutional and statutory provisions including International Conventions,decision and directions promulgated by the Apex Court of India and the NHRC, there is a constant increasein the custodial torture, custodial death and custodial ill-treatment which is a disturbing factor that causesdeep anxiety in the society. The Prevention of Anti-Torture Act is the need of the hour